2007
DOI: 10.1038/sj.emboj.7601723
|View full text |Cite
|
Sign up to set email alerts
|

ERK1/2-dependent phosphorylation of BimEL promotes its rapid dissociation from Mcl-1 and Bcl-xL

Abstract: The proapoptotic protein Bim is expressed de novo following withdrawal of serum survival factors. Here, we show that BimÀ/À fibroblasts and epithelial cells exhibit reduced cell death following serum withdrawal in comparison with their wild-type counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
175
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(187 citation statements)
references
References 47 publications
(113 reference statements)
10
175
1
Order By: Relevance
“…32,34,35 This study provides evidence that LX might affect these pathways. Incubation of macrophages with staurosporine induces a rapid activation of JNK and p38 MAPKs, but not of ERK, a classic survival pathway.…”
Section: Discussionmentioning
confidence: 86%
“…32,34,35 This study provides evidence that LX might affect these pathways. Incubation of macrophages with staurosporine induces a rapid activation of JNK and p38 MAPKs, but not of ERK, a classic survival pathway.…”
Section: Discussionmentioning
confidence: 86%
“…Two other BH3-only proteins, BIM and PUMA, stabilize MCL-1 via a mechanism that requires their BH3 domains, 21,37 and interaction of BIM EL with BCL-2 also reduces its turnover. 38 Although further studies are required to reconcile these differing results, together they highlight the critical role that interactions between BH3-only proteins and their pro-survival partners have in regulating the stability of multiple BCL-2 family proteins.…”
Section: Discussionmentioning
confidence: 99%
“…24,29,30 More recently, it has been demonstrated that ERK1/2 activation can inhibit the binding of BIM EL to BCL-2 family proteins such as BCL-x L and MCL-1. 25,31 In serum-starved cells newly synthesized BIM EL associates with BCL-x L and MCL-1 but re-stimulation of cells with growth factors promotes the rapid dissociation of BIM EL :BCL-x L or BIM EL :MCL-1 complexes and activation of ERK1/2 is necessary and sufficient for this 25 (Figure 1). As BIM EL needs to engage with pro-survival proteins to kill cells this represents an additional survival mechanism.…”
Section: Erk1/2-dependent Regulation Of Bh3-only Proteinsmentioning
confidence: 99%
“…In addition to regulation of transcription, BIM EL is phosphorylated at multiple sites in response to selective activation of the ERK1/2 pathway 17 and this has the effect of promoting the ubiquitination and proteasome-dependent turnover of BIM EL 23 ( Figure 1). BIM EL is phosphorylated directly by ERK1/2 at up to four different sites; [24][25][26] the exon unique to BIM EL encodes three ERK1/2 phosphorylation sites and a DEF-type ERK1/2 docking domain. 27,28 Of these three Ser 69 (Ser 65 in mouse and rat) appears to be a key signal for BIM EL turnover as S 69 A or S 69 G mutants are defective in turnover, accumulate to higher levels than wild-type protein, and may exhibit enhanced toxicity.…”
Section: Erk1/2-dependent Regulation Of Bh3-only Proteinsmentioning
confidence: 99%